2010
DOI: 10.1371/journal.pone.0008555
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Eliciting Antibodies against Cryptic, Conserved, Conformationally Dependent Epitopes of HIV Envelope Glycoprotein

Abstract: BackgroundNovel strategies are needed for the elicitation of broadly neutralizing antibodies to the HIV envelope glycoprotein, gp120. Experimental evidence suggests that combinations of antibodies that are broadly neutralizing in vitro may protect against challenge with HIV in nonhuman primates, and a small number of these antibodies have been selected by repertoire sampling of B cells and by the fractionation of antiserum from some patients with prolonged disease. Yet no additional strategies for identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…The strategy to identify this cryptic epitope may be applicable to vaccine development for other organisms. 24,25 Our specific approach was to focus on the carboxyl-terminal region of the M protein, a major virulence factor for the organism. There was evidence that this relatively large but highly conserved carboxyl-terminal segment of the protein was capable of inducing protection in a mucosal challenge model.…”
Section: Discovery Of a Cryptic Vaccine Epitopementioning
confidence: 99%
“…The strategy to identify this cryptic epitope may be applicable to vaccine development for other organisms. 24,25 Our specific approach was to focus on the carboxyl-terminal region of the M protein, a major virulence factor for the organism. There was evidence that this relatively large but highly conserved carboxyl-terminal segment of the protein was capable of inducing protection in a mucosal challenge model.…”
Section: Discovery Of a Cryptic Vaccine Epitopementioning
confidence: 99%
“…Targeting of the conformational epitope has been more actively pursued in immunologic circles. In a recent study, Kelker and colleagues (44) showed that careful immunogen selection resulted in the generation of antibodies with promising therapeutic potential. By targeting cryptic, usually conserved epitopes in the gp120 protein of HIV, they also showed strong parallels with the development and therapeutic paradigm of mAb 806.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive production of such antibodies would obscure the infection-induced effect on the constitutive binding of the B-SAg determinant. For example, HIV infection induces a vigorous antibody response to the immunodominant gp120 epitopes, even as there is no appreciable antibody response to the B-SAg determinant of this protein (60,62). We suggest that the observed post-infection decrease of Efb cleaving activity accurately reflects the infection-induced antibody response directed solely to the putative B-SAg determinant.…”
Section: Discussionmentioning
confidence: 88%